UTILIZING CARBON NANOTUBES AS EFFICIENT NANOADSORBENT FOR PANTOPRAZOLE REMOVAL FROM AQUEOUS SAMPLES: KINETICS, ISOTHERM, AND THERMODYNAMIC STUDIES - Sadeghpour, Neda; Vadi, Mehdi; Bagheri, Narges (Journal of the Chilean Chemical Society, 2021)
In this work, carbon nanotubes (MWCNTs) were utilized as efficient adsorbents for pantoprazole (PP) removal. We used MWCNTs that were synthesized using the chemical vapor deposition process. The physical characteristics of MWCNTs were described by Brunauer-Emmett-Teller (BET) contact area, surface functional group analysis by the point of zero charge (pHPZC), Fourier transform infrared (FTIR) analysis, Scanning electron microscope (SEM), X-ray diffraction (XRD), and Transmission electron microscopy (TEM). The single-point BET surface area of the MWCNTs was found to be 98.7 m2 g-1, with the median pores’ diameter of 30.9 nm and an average pore(s) volume of 0.764 cm3 g-1. Effective parameters on the PP removal including, pH, contact time and initial amount of adsorbents were optimized, revealing maximum PP removal at pH=6.0 after 25.0 min when 0.026 g MWCNTs. The pseudo second-order kinetic model for adsorption of PP on the surface of both adsorbents revealed the high value of correlation coefficient, indicating the high ability of the pseudo second-order model for representation of experimental results. Adsorption equilibrium studies indicated that the Freundlich isotherm efficiently represented MWCNTs adsorption data. The thermodynamic parameters (Gebbs free energy, enthalpy, and entropy) of adsorption process were calculated. Results had shown that adsorption of PP on the MWCNTs is feasible, spontaneous, and exothermic process in the temperature range of 25-76 °C.